Ceramic coating slurry for lithium battery separator and preparation method thereof
Patent Information
- Application Number
- CN202211715894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-12-29
AI Technical Summary
虽然在隔膜上涂覆一层陶瓷涂层后隔膜的抗异物和耐热性等较基膜有很大改善,但是陶瓷涂层与极片的粘合性极低,可能会导致隔膜与极片分离,存在安全性的问题
[0039] 1. The average particle size of the microcapsule-type binder is larger than that of the inorganic nanoparticles. This causes the microcapsule-type binder to protrude from the surface of other components when the ceramic coating slurry is applied to the base film. Before the ceramic coating slurry dries, the lithium battery electrode and separator are pressed together. The microcapsules rupture, releasing the binder. Under the pressure of the battery electrode and separator, the binder adheres uniformly to the ceramic coating and electrode, improving the stability of the adhesion between the separator and the electrode, and also improving the adhesion between the ceramic coating and the base film. Since binders themselves do not possess good lithium-ion permeability, the microcapsule-type binder maximizes the adhesive effect of the binder, reducing unnecessary addition and use of binders, and better improving the lithium-ion permeability of the separator.
Smart Images

Figure BDA0004027786030000071 
Figure BDA0004027786030000081 
Figure BDA0004027786030000111
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium batteries, and in particular to a ceramic coating slurry for lithium battery separators and its preparation method. Background Technology
[0002] Currently, the separators used in lithium-ion batteries are generally polyolefin porous membranes. Because these polyolefin porous membranes have a low melting point, they are prone to shrinkage or melting when the battery temperature rises, causing a short circuit between the positive and negative electrodes, which can then lead to combustion and explosion. Therefore, in order to improve the thermal stability and mechanical strength of the separator, a ceramic coating is usually applied to it.
[0003] In existing technologies, inorganic ceramic particles and binders are generally mixed into a slurry, which is then coated onto the separator to form a ceramic coating. Although coating the separator with a ceramic coating greatly improves its resistance to foreign matter and heat resistance compared to the base membrane, the adhesion between the ceramic coating and the electrode is extremely low, which may cause the separator to separate from the electrode, posing a safety issue.
[0004] In response to this situation, the usual practice is to coat the separator with a ceramic coating and then apply an adhesive layer on top of the ceramic coating to bond the separator and the electrode. However, this method increases the complexity of the process, requiring an additional layer of adhesive, so there is still room for improvement. Summary of the Invention
[0005] To further improve the adhesion between the separator and the electrode without requiring additional adhesive coating, this application provides a ceramic coating slurry for lithium battery separators and its preparation method. A thickener, formulated with sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate in a mass ratio of (5-15):(10-20):(1-10):(1-10), can increase the viscosity of the ceramic coating slurry when standing, improve its fluidity when stirred, further promote the uniform distribution of microencapsulated adhesives in the ceramic coating slurry, and further enhance the adhesion of the ceramic coating slurry to the separator.
[0006] Firstly, the ceramic coating slurry for a lithium battery separator provided in this application adopts the following technical solution:
[0007] A ceramic coating slurry for a lithium battery separator, comprising, by weight, 60-70 parts of inorganic nanoparticles, 2-5.5 parts of thickener, 5-10 parts of microcapsule binder, and 50-60 parts of deionized water. The thickener is a compound of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate in a weight ratio of (5-15):(10-20):(1-10):(1-10). The average particle size of the microcapsule binder is larger than the average particle size of the inorganic nanoparticles.
[0008] In the above technical solution, the average particle size of the microcapsule-type binder is larger than that of the inorganic nanoparticles. This causes the microcapsule-type binder to protrude from the surface of other components when the ceramic coating slurry is applied to the base film. Before the ceramic coating slurry is completely dry, the lithium battery electrode and separator are pressed together. The microcapsules rupture, releasing the binder inside. Under the pressure of the battery electrode and separator, the binder adheres uniformly to the ceramic coating and the electrode. This method eliminates the need to apply another layer of adhesive to the ceramic coating, making the operation more convenient. It also improves the stability of the adhesion between the separator and the electrode, as well as the adhesion between the ceramic coating and the base film. Because binders themselves do not have good lithium electron permeability, the microcapsule-type binder maximizes the use of the binder's adhesive effect, reducing unnecessary addition and use of binders, and better improving the lithium electron permeability of the separator.
[0009] In the above technical solution, the addition of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate to the ceramic coating slurry can maintain the required fluidity for coating during stirring, promote the homogeneity of the ceramic coating slurry, significantly reduce the amount of deionized water added to the ceramic coating slurry, and reduce the probability of unstable adhesion between ceramic particles and the base membrane of the diaphragm due to the high fluidity of deionized water itself; when standing, it will increase the viscosity of the ceramic coating slurry, which can improve the suspension stability of solids in the ceramic coating slurry. During coating, ceramic particles can be more easily and evenly coated on the base membrane of the diaphragm, and when the coating is completed, the adhesion of the ceramic coating slurry to the base membrane of the diaphragm is increased, so that the ceramic coating slurry will not fall off or shift when it naturally adheres to the base membrane, reducing the probability of subsequent ceramic particles falling off the base membrane, and further improving the overall heat resistance and foreign matter resistance of the diaphragm.
[0010] Microencapsulated binders can be uniformly distributed in ceramic coating slurries through thickeners. Furthermore, sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate can significantly improve the viscosity of ceramic coating slurries during standing, further enhancing the stability of microencapsulated binders in ceramic coating slurries and reducing their deposition. When ceramic coating slurries are applied to base membranes, the high viscosity of the ceramic coating slurries allows the microencapsulated binders to adhere stably to the base membrane without displacement, which further improves the adhesion between the diaphragm and the electrode.
[0011] Preferably, the microcapsule-type binder includes a shell and a core, wherein the shell is chitosan.
[0012] In the above technical solution, the capsule shell is chitosan. Chitosan molecules contain amino and etheroxy groups, which can complex with lithium ions. Chitosan does not hinder the passage of lithium ions. As the capsule shell material of microcapsules, chitosan does not affect the overall lithium ion penetration performance of the membrane.
[0013] Preferably, the core is a sodium hexametaphosphate binder.
[0014] In the above technical solution, sodium hexametaphosphate, as a binder, has excellent high temperature resistance and stability, can promote the polymerization of ceramic particles, and can also absorb excess deionized water in the ceramic coating slurry. The ceramic particles can better adhere to the base film, and can also improve the adhesion between the ceramic coating and the electrode.
[0015] By encapsulating sodium hexametaphosphate binder within chitosan, the contact and polymerization reaction between sodium hexametaphosphate and inorganic nanoparticles within the ceramic coating slurry is avoided. After the inorganic nanoparticles and microcapsule binder are evenly distributed on the separator's base film, the microcapsules are broken by pressing the electrode sheet against the separator, releasing the binder. The binder and inorganic nanoparticles react, further improving the uniformity of the ceramic coating thickness, increasing the evenness of the inorganic nanoparticle distribution on the separator's base film, promoting the adhesion between the inorganic nanoparticles and the separator, and enhancing the adhesion between the electrode sheet and the separator. This further improves the separator's heat resistance and reduces the impact of the ceramic coating on lithium-ion permeability.
[0016] Preferably, the core-to-shell ratio of the microcapsule-type adhesive is 1:(1-2).
[0017] In the above technical solution, the core-to-shell ratio of the microcapsule binder is limited to 1:(1-2). This makes the microcapsule binder easier to break when coated onto the electrode, reducing the likelihood of it failing to break due to the shell being too large. This allows for better utilization of the binder encapsulated within the microcapsule binder, resulting in a stronger bond between the diaphragm and the electrode.
[0018] Preferably, the mass ratio of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate is 4:7:2:2.
[0019] In the above technical solution, the thickener prepared according to the above mass ratio can better improve the adhesion of the ceramic coating slurry, and the ceramic coating slurry can better adhere to the base film of the separator, thereby improving the heat resistance and foreign matter resistance of the lithium battery base film.
[0020] Preferably, the mass ratio of the inorganic nanoparticles, thickener, microcapsule binder, and deionized water is 70:3:8:50.
[0021] In the above technical solution, the ceramic coating slurry prepared according to the above mass ratio has better viscosity when it is in a static state. The suspended particles in the slurry can be more stably and uniformly dispersed in the slurry, and the deposition of suspended particles in the slurry is further reduced. At the same time, the ceramic coating slurry has better fluidity when stirred, and the ceramic coating slurry can be more easily and uniformly attached to the base membrane of the diaphragm.
[0022] Preferably, the inorganic nanoparticles have an average particle size of 100–500 nm, and the microcapsule-type binder has an average particle size of 1–10 μm.
[0023] In the above technical solution, the inorganic nanoparticles and microcapsule-type binders with the above-mentioned particle size can further promote the fluidity and adhesion of the ceramic coating slurry.
[0024] Preferably, the preparation method of the microcapsule-type adhesive includes the following steps:
[0025] (1) Dissolve sodium hexametaphosphate and chitosan in a 2wt% acetic acid solution at a mass ratio of 1:(1~2) to prepare a sodium hexametaphosphate chitosan acetic acid solution.
[0026] (2) Add the sodium hexametaphosphate chitosan acetate solution dropwise to liquid paraffin containing emulsifier, at a temperature range of 40-60℃ and a fixed rotation speed of 2000-2500 rpm, and stir emulsify for 15-20 minutes to obtain mixed solution A.
[0027] (3) Adjust the pH of the A mixture to 5-6, then add the cross-linking curing agent and cure for two hours to obtain the B mixture;
[0028] (4) The B mixture solution was separated by centrifugation, washed and dried to obtain a microcapsule adhesive.
[0029] In the above technical solution, the microcapsule adhesive prepared by first emulsifying the solution, then adjusting the pH value, and finally adding the crosslinking curing agent has a more uniform particle size and better encapsulation.
[0030] Preferably, in step 3 of the preparation method of the microcapsule adhesive, the pH of mixed solution A is adjusted to 5.
[0031] In the above technical solution, the pH of solution A in step 3 is adjusted to 5, which makes the structure of the prepared capsule-type adhesive more stable and less prone to breakage.
[0032] Secondly, the method for preparing a ceramic coating slurry for a lithium battery separator provided in this application adopts the following technical solution:
[0033] A method for preparing a ceramic coating slurry for a lithium battery separator includes the following steps:
[0034] (1) Add the inorganic nanoparticles, thickener and deionized water into a reaction vessel, with a temperature range of 40-60℃ and a stirring rate of 180-250rpm, and stir for 1-2 hours to obtain a mixed slurry.
[0035] (2) Add the microcapsule-type binder to the mixed slurry, with a temperature range of 40-60℃ and a stirring rate of 180-250rpm, and stir for 1-2 hours to obtain a ceramic coating slurry for lithium battery separator.
[0036] In the above technical solution, other components besides the microcapsule binder are mixed first to prevent the microcapsule binder from rupturing prematurely due to the huge friction between it and the inorganic nanoparticles during pouring. This two-step addition of components and stirring method can minimize the probability of the microcapsule binder breaking during stirring.
[0037] The inorganic nanoparticles are one or more of aluminum oxide, silicon dioxide, titanium dioxide, zirconium dioxide, magnesium oxide, zinc oxide, barium oxide, and calcium carbonate in any proportion.
[0038] In summary, this application includes at least one of the following beneficial technical effects:
[0039] 1. The average particle size of the microcapsule-type binder is larger than that of the inorganic nanoparticles. This causes the microcapsule-type binder to protrude from the surface of other components when the ceramic coating slurry is applied to the base film. Before the ceramic coating slurry dries, the lithium battery electrode and separator are pressed together. The microcapsules rupture, releasing the binder. Under the pressure of the battery electrode and separator, the binder adheres uniformly to the ceramic coating and electrode, improving the stability of the adhesion between the separator and the electrode, and also improving the adhesion between the ceramic coating and the base film. Since binders themselves do not possess good lithium-ion permeability, the microcapsule-type binder maximizes the adhesive effect of the binder, reducing unnecessary addition and use of binders, and better improving the lithium-ion permeability of the separator.
[0040] 2. The addition of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate to the ceramic coating slurry maintains the required fluidity for coating during stirring, promotes homogenization of the slurry, significantly reduces the amount of deionized water added, and decreases the likelihood of unstable adhesion between ceramic particles and the membrane substrate due to the high fluidity of deionized water. During settling, the viscosity of the ceramic coating slurry increases, improving the suspension stability of solids within it. During coating, ceramic particles can be more easily and evenly coated onto the membrane substrate. Furthermore, the increased adhesion of the ceramic coating slurry to the membrane substrate after coating prevents detachment or displacement, reducing the likelihood of subsequent ceramic particle detachment and further improving the overall heat resistance and foreign matter resistance of the membrane.
[0041] 3. By encapsulating sodium hexametaphosphate binder within chitosan, the contact and polymerization reaction between sodium hexametaphosphate and inorganic nanoparticles within the ceramic coating slurry is avoided. After the inorganic nanoparticles and microcapsule binder are evenly distributed on the separator's base film, the microcapsules are broken by pressing the electrode sheet against the separator, releasing the binder. The binder and inorganic nanoparticles react, further improving the uniformity of the ceramic coating thickness, increasing the evenness of the inorganic nanoparticle distribution on the separator's base film, promoting the adhesion between the inorganic nanoparticles and the separator, and enhancing the adhesion between the electrode sheet and the separator. This further improves the separator's heat resistance and reduces the impact of the ceramic coating on lithium-ion permeability. Detailed Implementation
[0042] The following will provide a detailed description of a ceramic coating slurry for a lithium battery separator and its preparation method, with reference to specific embodiments. However, the embodiments of the present invention are not limited thereto.
[0043] Examples 1-3
[0044] A ceramic coating slurry for a lithium battery separator, wherein the amounts of each component are shown in Table 1.
[0045] Table 1. Amounts of each component added in Examples 1-3
[0046]
[0047]
[0048] The preparation of ceramic coating slurries in Examples 1-3 includes:
[0049] Step 01) Add inorganic nanoparticles (average particle size of 100-500 nm), sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, sodium silicate, and deionized water to a reaction vessel and stir at 200 r / min for 1.5 h at 50 °C to obtain a mixed slurry.
[0050] Step 02) Add the microcapsule-type binder to the mixed slurry and stir at 200 r / min for 1 h at 50°C to obtain the ceramic coating slurry.
[0051] Preparation of microcapsule-type adhesives in Examples 1-3:
[0052] Step 1) Dissolve sodium metaphosphate and chitosan in a 2 wt% acetic acid solution at a mass ratio of 1:2 to prepare a chitosan acetic acid solution containing 2 wt% sodium metaphosphate; prepare liquid paraffin containing Span-80 in a volume ratio of 24:1; at 50°C, mechanically stir the liquid paraffin containing Span-80 at 200 rpm / min and add the sodium metaphosphate chitosan acetic acid solution dropwise to obtain the first mixture.
[0053] Step 2) Add sodium hydroxide solution (1 mol / L) dropwise to the first mixture to adjust the pH of the first mixture to 5. Then, under 50°C, stir and emulsify at a fixed speed of 2500 rpm for 15 min to obtain the second mixture.
[0054] Step 3) Add glutaraldehyde to the second mixture and cure at 50°C for two hours to obtain the third mixture.
[0055] Step 4) After centrifugation, the solid of the third mixture is taken out. The solid is washed with petroleum ether, acetone and deionized water in sequence and then vacuum dried at 30°C for 48 hours to obtain microcapsule adhesive.
[0056] Example 4
[0057] Unlike Example 3, in the preparation of the ceramic coating slurry, in step 01, the amount of sodium carboxymethyl cellulose added is 0.8 kg, the amount of polyethylene oxide added is 1.4 kg, the amount of polycarboxylic acid ammonium salt added is 0.4 kg, and the amount of sodium silicate added is 0.4 kg.
[0058] Example 5
[0059] Unlike Example 3, the preparation of the microcapsule-type adhesive involved dissolving sodium metaphosphate and chitosan in a 1:1 mass ratio in a 2wt% acetic acid solution to prepare a chitosan acetic acid solution containing 2wt% sodium metaphosphate.
[0060] Example 6
[0061] Unlike Example 3, in the preparation of the microcapsule adhesive, sodium hydroxide solution (1 mol / L) was added dropwise to the first mixture in step 2 to adjust the pH of the first mixture to 6.
[0062] Comparative Example 1
[0063] Unlike Example 3, in the preparation of the ceramic coating slurry, in step 01, sodium carboxymethyl cellulose was replaced with an equal amount of hydroxyethyl cellulose.
[0064] Comparative Example 2
[0065] Unlike Example 3, in the preparation of the ceramic coating slurry, in step 01, polyethylene oxide was replaced with an equal amount of hydroxyethyl cellulose.
[0066] Comparative Example 3
[0067] Unlike Example 3, in the preparation of the ceramic coating slurry, in step 01, the polycarboxylate ammonium salt was replaced with an equal amount of hydroxyethyl cellulose.
[0068] Comparative Example 4
[0069] Unlike Example 3, in the preparation of the ceramic coating slurry, sodium silicate was replaced with an equal amount of calcium silicate in step 01.
[0070] Comparative Example 5
[0071] Unlike Example 3, in the preparation of the ceramic coating slurry, in step 01, the amount of deionized water added was 70 parts.
[0072] Comparative Example 6
[0073] Unlike Example 3, the preparation of the microencapsulated binder is omitted. In the preparation of the ceramic coating slurry, the microencapsulated binder is replaced with an equal amount of sodium hexametaphosphate. The preparation method of the ceramic coating slurry becomes:
[0074] Inorganic nanoparticles (average particle size of 100-500 nm), sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, sodium silicate, sodium hexametaphosphate, and deionized water were added to a reaction vessel and stirred at 200 r / min for 1.5 h at 50 °C to obtain a ceramic coating slurry.
[0075] Experiment 1
[0076] The distribution of microcapsule-type binders in ceramic coating slurry was observed using laser resonant electron microscopy.
[0077] Experimental method: The ceramic coating slurries of the above embodiments and comparative examples were coated onto a transparent membrane using a coating machine. After the ceramic coating slurry dried, the membrane was cut into 70mm*30mm squares and placed under a laser resonance electron microscope (FV3000) to observe the distribution of the microcapsule-type adhesive.
[0078] Experimental results: Through observation, the microcapsule-type binders in Examples 1-6 were uniformly distributed, while the microcapsule-type binders in the ceramic coating slurries of Comparative Examples 1-5 were partially bonded together, and the distribution gaps between the microcapsule-type binders were uneven.
[0079] Experiment 2
[0080] When a slurry flows, internal friction occurs between molecules. This property is called the viscosity of a liquid. The magnitude of viscosity is expressed by viscosity, which can characterize the flowability of the slurry. The flowability of the ceramic coating slurry when it is stirred is determined by testing its viscosity.
[0081] Experimental Method: Viscosity was measured using an NDJ-9S viscometer (Shanghai Fangrui Instrument Co., Ltd.). The ceramic coating slurries for each experimental example and comparative example were poured into beakers. The viscosity was measured using rotor #1 of the NDJ-9S viscometer. During measurement, the surface of the ceramic coating slurry was kept aligned with the rotor's scale. The viscosity value was read after the slurry stabilized. The experimental results are shown in Table 2.
[0082] Table 2 Viscosity values of ceramic coating slurry
[0083]
[0084]
[0085] Experimental data show that the viscosity of the ceramic coating slurry containing sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate is only slightly higher than that of the ceramic coating slurry containing a large amount of deionized water when stirred. This means that even with a significant reduction in the amount of deionized water added, the combination of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate can still maintain good fluidity of the ceramic coating slurry when stirred. The microcapsule-type binder and inorganic nanoparticles can be uniformly dispersed in the ceramic coating slurry. This reduces the influence of deionized water when preparing the ceramic coating for the lithium battery separator, and allows the microcapsule-type binder and inorganic nanoparticles to be more uniformly coated on the base film of the battery separator, further improving the performance of the lithium battery.
[0086] Experiment 3
[0087] The sag test was used to test the flowability of the ceramic coating slurry during stirring and when it was left to stand.
[0088] Experimental method: Take a smooth and flat glass plate with a surface of 200*200mm, place it on a flat table, and tilt it at an angle of 30° to the table. Mark a titration line 10mm away from the top of the glass plate.
[0089] Using a graduated disposable Pasteur pipette (1ml size), 1ml of ceramic coating slurry from each example and comparative example was taken and dropped onto the titration line from a height of 2mm above the titration line on a clean glass plate within 1 second. The flow distance S1 of the ceramic coating slurry within 30 seconds was measured.
[0090] Using a graduated disposable Pasteur pipette (1ml size), 1ml of the ceramic coating slurry from each example and comparative example, which is being continuously stirred, is dropped onto the titration line from a height of 2mm above the line on a clean glass plate within 1 second. The flow distance S2 of the ceramic coating slurry is measured within 30 seconds.
[0091] The experimental results are shown in Table 3.
[0092] Table 3 Flowability of Ceramic Coating Slurry
[0093] Experimental Example 1 23 59 Experimental Example 2 25 61 Experimental Example 3 21 53 Experiment Example 4 17 49 Experimental Example 5 28 60 Experimental Example 6 26 53 Comparative Example 1 36 38 Comparative Example 2 31 32 Comparative Example 3 35 37 Comparative Example 4 38 40 Comparative Example 5 63 65 Comparative Example 6 25 24
[0094] Experimental data show that the ceramic coating slurry with added sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate has increased viscosity when standing, which can improve the suspension stability of solids in the ceramic coating slurry. When stirred, its fluidity increases, which can maintain the fluidity required for coating and significantly reduce the amount of deionized water added to the ceramic coating slurry.
[0095] Experiment 4
[0096] A microcomputer-controlled electronic universal testing machine was used to determine the peel strength of the diaphragm and the electrode by a 180° peel test, thereby testing the adhesion between the diaphragm and the electrode.
[0097] Experimental methods:
[0098] Adhesion between lithium battery separator and electrode:
[0099] The ceramic coating slurries of the above embodiments and comparative examples are coated onto the base film of the lithium battery separator using a coating machine. Before the ceramic coating slurry dries, the lithium battery electrode and the base film of the lithium battery separator are pressed together using a roller press. Finally, the base film of the separator and the ceramic coating slurry of the electrode that have been adhered to the lithium battery are vacuum dried at 30°C for 48 hours, and the lithium battery separator and the electrode adhere.
[0100] Peel strength test:
[0101] The test temperature was 25℃ and the relative humidity was 50%. The diaphragms with adhered electrodes were cut to 80mm x 25mm pieces. One side of the electrode was bent inwards by 180°, and the electrode was peeled off the diaphragm by approximately 1mm. The electrode and diaphragm were fixed to the upper and lower clamps, ensuring the sensor was not under stress. The computer-controlled electronic universal testing machine was turned on, the 180° peel force test was selected, and the peel speed was set to 100mm / min. The test was then started. Each of the above embodiments and comparative examples was tested three times, and the average value was taken. The peel strength (N / m) of the diaphragm and electrode was tested, and the results are shown in Table 4.
[0102] Table 4. Results of peel strength tests on diaphragms and electrodes.
[0103] Experimental Example 1 121 Experimental Example 2 124 Experimental Example 3 123 Experiment Example 4 128 Experimental Example 5 118 Experimental Example 6 114 Comparative Example 1 66 Comparative Example 2 69 Comparative Example 3 58 Comparative Example 4 86 Comparative Example 5 85 Comparative Example 6 109
[0104] Experimental data show that the addition of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate to the ceramic coating slurry can significantly improve the homogeneity of the microcapsule binder in the ceramic coating slurry. This allows the microcapsule binder to be uniformly coated on the base membrane of the separator. When the separator and the electrode adhere, after the microcapsule binder ruptures, the binder inside the capsule core can be uniformly dispersed between the separator and the electrode, resulting in better adhesion between the separator and the electrode. This reduces the occurrence of ceramic coating detachment and makes the lithium battery safer and more stable during operation.
[0105] Experiment 5
[0106] The safety of batteries using ceramic-coated slurry was determined using impact and nail penetration tests. The impact test simulates a heavy object falling freely from a height onto the battery surface, causing the battery's internal components to be compressed under the force of gravity. This test examines whether the battery can maintain safety when the separator fails to effectively isolate the positive and negative electrodes. The nail penetration test involves inserting a nail into the battery and piercing the casing, causing a short circuit between adjacent electrodes and exposing the electrolyte to air.
[0107] Experimental methods:
[0108] Preparation of ceramic coating for lithium battery separator:
[0109] The ceramic coating slurry is coated onto the base film of the lithium battery separator using a coating machine. Before the ceramic coating slurry dries, the lithium battery electrode and the base film of the lithium battery separator are pressed together using a roller press. Finally, the base film of the separator and the ceramic coating slurry of the electrode that have been adhered to the lithium battery are vacuum dried at 30°C for 48 hours, and the lithium battery separator and electrode adhere.
[0110] All prepared lithium battery separators and electrodes were assembled into lithium batteries using the same method and fully charged, as used in the experimental and comparative examples.
[0111] Impact test: Place a fully charged battery at the bottom of the impact device, place a 16mm diameter rod on the surface of the battery cell, and then drop a 10kg weight from a height to impact the battery head-on. Observe whether the battery catches fire or explodes, and record the results.
[0112] Needle puncture: Use a stainless steel needle with a diameter of 3mm to puncture the center of a fully charged battery, leave it for 1 hour, observe whether the battery catches fire or explodes, and record the results.
[0113] The experimental results are shown in Table 5.
[0114] Table 5 Results of the impact and needle puncture tests
[0115] Experimental Example 1 No fire or explosion No fire or explosion Experimental Example 2 No fire or explosion No fire or explosion Experimental Example 3 No fire or explosion No fire or explosion Experiment Example 4 No fire or explosion No fire or explosion Experimental Example 5 No fire or explosion No fire or explosion Experimental Example 6 No fire or explosion No fire or explosion Comparative Example 1 fire fire Comparative Example 2 fire fire Comparative Example 3 fire fire Comparative Example 4 fire fire Comparative Example 5 smoke smoke Comparative Example 6 smoke smoke
[0116] Experimental data show that ceramic coatings prepared by adding sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate to the ceramic coating slurry have a better effect on improving the stability of the separator and can further improve the safety of lithium batteries.
[0117] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A ceramic coating slurry for a lithium battery separator, characterized in that, The product comprises, by weight, 60-70 parts inorganic nanoparticles, 2-5.5 parts thickener, 5-10 parts microcapsule binder, and 50-60 parts deionized water. The thickener is a compound of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate in a weight ratio of (5-15):(10-20):(1-10):(1-10). The average particle size of the microcapsule binder is larger than the average particle size of the inorganic nanoparticles. The microcapsule-type binder includes a shell and a core, wherein the shell is chitosan and the core is sodium hexametaphosphate binder; The preparation method of the microcapsule-type adhesive includes the following steps: (1) Dissolve sodium hexametaphosphate and chitosan in a 2wt% acetic acid solution at a mass ratio of 1:(1~2) to prepare a sodium hexametaphosphate-chitosan-acetic acid solution; (2) Add the sodium hexametaphosphate chitosan acetate solution dropwise to liquid paraffin containing emulsifier, at a temperature range of 40~60℃ and a fixed rotation speed of 2000~2500rpm, and stir emulsify for 15~20min to obtain mixed solution A. (3) Adjust the pH of the A mixture to 5-6, then add the cross-linking curing agent and cure for two hours to obtain the B mixture; (4) The B mixture solution was separated by centrifugation, washed and dried to obtain a microcapsule adhesive.
2. The ceramic coating slurry for a lithium battery separator according to claim 1, characterized in that, The core-to-shell ratio of the microcapsule-type adhesive is 1:(1~2).
3. The ceramic coating slurry for a lithium battery separator according to claim 1, characterized in that, The mass ratio of sodium carboxymethyl cellulose, polyethylene oxide, ammonium polycarboxylate, and sodium silicate is 4:7:2:
2.
4. The ceramic coating slurry for a lithium battery separator according to claim 1, characterized in that, The mass ratio of the inorganic nanoparticles, thickener, microcapsule binder, and deionized water is 70:3:8:
50.
5. The ceramic coating slurry for a lithium battery separator according to claim 1, characterized in that, The inorganic nanoparticles have an average particle size of 100~500nm, and the microcapsule-type binder has an average particle size of 1~10μm.
6. The ceramic coating slurry for a lithium battery separator according to claim 5, characterized in that, In step (3) of the preparation method of the microcapsule adhesive, the pH of the A mixed solution is adjusted to 5.
7. A method for preparing a ceramic coating slurry for a lithium battery separator as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Add the inorganic nanoparticles, thickener and deionized water into a reaction vessel, with a temperature range of 40~60℃ and a stirring rate of 180~250rpm, and stir for 1~2h to obtain a mixed slurry; (2) Add the microcapsule-type binder to the mixed slurry, with a temperature range of 40~60℃ and a stirring rate of 180~250rpm, and stir for 1~2h to obtain a ceramic coating slurry for lithium battery separator.
Citation Information
Patent Citations
Adhesive for mounting mobile phone
CN106010314A
Diaphragm of lithium battery and preparation method thereof
CN106887559A